Determination and evaluation of principal minerals in Negella sativa by atomic absorption technical methods (Baghdad Science Journal, 2011)
Determination and evaluation of principal minerals in Negella sativa by atomic absorption technical methods were showed, using wet ashing method. This work was done on Negella sativa because of wide using of this plant in many formulations ( in food or medicine ).two types of atomic absorptions were used : first, flame atomic absorption spectroscopy, for minerals of high concentrations such as, Na, Mg, K, Fe, Ca, Li, Ni, Zn, Mn, Cu. Second, flameless atomic absorption spectroscopy, for minerals of low concentrations such as, Al, Si, V, B, Pb, Co, Cd, Cr ,Si, Hg, Sn .The results showed the existence of many minerals in Negella sativa useful to human sanity with acceptable dietary allowance. On other side, the presence of harmful minerals to human sanity(Pb, Cd, Hg ) were negligible.